Reduction in MCP-1 production in preadipocytes is mediated by PPARγ activation and JNK/SIRT1 signaling - Sawamoto, Atsushi; Itagaki, Ibuki; Okuyama, Satoshi; Nakajima, Mitsunari (Biochimica et biophysica acta. General subjects, 2025)
Obesity-induced monocyte chemoattractant protein 1 (MCP-1) production leads to the infiltration of monocytes/macrophages into white adipose tissue (WAT), which contributes to systemic insulin resistance. Peroxisome proliferator-activated receptor gamma (PPARγ) agonists are known to reduce MCP-1 production in both humans and mice; however, the underlying mechanism in WAT remains unclear. Here, we propose a novel mechanism for the reduction in MCP-1 production in preadipocytes. The PPARγ agonist rosiglitazone (RSG) reduced MCP-1 production and secretion in response to lipopolysaccharide (LPS) in 3T3-L1 preadipocytes and mouse stromal vascular fraction–derived primary preadipocytes. Both RSG and SP600125 (a c-Jun N-terminal kinase (JNK) inhibitor) inhibited LPS-induced degradation of silent information regulator 2 homolog 1 (SIRT1), a negative regulator of MCP-1 production in 3T3-L1 preadipocytes. Furthermore, RSG inhibited LPS-induced activation of nuclear factor-κB. These effects of RSG were abolished in 3T3-L1 preadipocytes transfected with Pparg siRNA. These findings highlight a novel mechanism by which PPARγ activation inhibits JNK/SIRT1 signaling in preadipocytes and contributes to the reduction in MCP-1 production, suggesting that preadipocytes could be a potential therapeutic target for the treatment of insulin resistance. •PPARγ is required for the reduction in LPS-induced MCP-1 production in 3T3-L1 and SVF-derived preadipocytes.•Rosiglitazone, a PPARγ agonist, inhibits the activation of JNK and degradation of SIRT1 in 3T3-L1 and SVF-derived preadipocytes.•Inhibition of the JNK/SIRT1 signaling pathway in preadipocytes may be a key mechanism underlying the reduction in MCP-1 production.